2020
DOI: 10.13106/jafeb.2020.vol7.no11.357
|View full text |Cite
|
Sign up to set email alerts
|

The S-Shaped Relationship Between Internationalization and Performance: Empirical Evidence from Laos

Abstract: The purpose of this study is to investigate the impact of internationalization on the business performance of firms in Laos as a transition economy. Using a panel dataset collected by the World Bank for 285 firms during the period 2009, 2012, and 2016 in the service and manufacturing industries, the two-steps Heckman regression results found robust evidence for the fact that the S-curve tie exists between the degree of internationalization and business performance of firms in Laos while controlling other facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…OC and EM were found to have significant positive role over MP duly supported by a number of previous investigation carried out by Hasyim et al. (2021), Pham (2021), Talukder and Jan (2017), Yousaf et al. (2015), Martín and Herrero (2012), Haines et al.…”
Section: Discussion Of Resultssupporting
confidence: 67%
“…OC and EM were found to have significant positive role over MP duly supported by a number of previous investigation carried out by Hasyim et al. (2021), Pham (2021), Talukder and Jan (2017), Yousaf et al. (2015), Martín and Herrero (2012), Haines et al.…”
Section: Discussion Of Resultssupporting
confidence: 67%
“…In the previous studies, it has been found that health employees (doctors, nurses, midwives, medical secretaries, and others) had a high perception of inclusive leadership toward their managers (Gül & Çakıcı, 2021). However, in studies conducted only with nurses, the perception of inclusive leadership was found to be low (Taie & Zoromba, 2022) and above average (Aslan et al, 2021;Wang et al, 2019).…”
Section: Inclusive Leadershipmentioning
confidence: 91%
“…Accordingly, employees are more motivated to fulfill their roles and make more cognitive, emotional, and physical contributions to the organization (Choi et al, 2015). Previous studies have revealed that inclusive leadership has a positive relationship with employees' work engagement (Aslan et al, 2021;Bao et al, 2021;Choi et al, 2015;Wang et al, 2019). Some studies have also found that inclusive leadership indirectly affects work engagement through psychological safety (Aslan et al, 2021;Nembhard & Edmondson, 2006) and employee creativity (Carmeli et al, 2010;Suk et al, 2015).…”
Section: The Relationship Between Inclusive Leadership With Work Enga...mentioning
confidence: 99%
“…On the global stage, CG has witnessed widespread research in an endeavour to determine its impact on various management variables affecting a firm's performance. A recent study by Phan and Duong (2021) showed that board structure is positively associated with a firm's performance, whereas age of the firm is negatively associated. Al-ahdal et al (2020) observed that board accountability does not have a significant impact on firms' performance measured by return on equity and Tobin's Q.…”
Section: Studies Conducted In All Over the Worldmentioning
confidence: 99%